The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1016/s0014-5793(01)02157-3
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and copper bind to unique sites of histatin 5

Abstract: Metal binding has been suggested to be relevant in the antifungal and antibacterial mechanism of histatin 5, a human salivary protein. Proton nuclear magnetic resonance (NMR) spectra were obtained to investigate the specificity of metal binding to the seven histidyl, one aspartyl and one glutamyl amino acid side-chains of histatin 5 in aqueous solutions. Three C O1^H histidyl and the C Q^H glutamyl resonances of histatin 5 were selectively altered in spectra of solutions containing three equivalents of zinc. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 27 publications
2
75
1
1
Order By: Relevance
“…131,132 There is also evidence that histatin 1 and to a lesser extent histatin 3 and 5 are incorporated into the enamel pellicle by crosslink reactions catalysed by oral transglutaminase. 133 The first three residues (DSH) of histatins 3 and 5 represent the ATCUN motif, which complexes Cu 2+ and Ni 2+ ions (Grogan et al 2001). 134 Furthermore, two Zn 2+ -binding motifs (HEXXH) are present in histatin 1, and one such motif is present in histatins 3 and 5.…”
Section: Histatins: Candidacidal and Wound-closure Stimulating Amps Imentioning
confidence: 99%
See 1 more Smart Citation
“…131,132 There is also evidence that histatin 1 and to a lesser extent histatin 3 and 5 are incorporated into the enamel pellicle by crosslink reactions catalysed by oral transglutaminase. 133 The first three residues (DSH) of histatins 3 and 5 represent the ATCUN motif, which complexes Cu 2+ and Ni 2+ ions (Grogan et al 2001). 134 Furthermore, two Zn 2+ -binding motifs (HEXXH) are present in histatin 1, and one such motif is present in histatins 3 and 5.…”
Section: Histatins: Candidacidal and Wound-closure Stimulating Amps Imentioning
confidence: 99%
“…133 The first three residues (DSH) of histatins 3 and 5 represent the ATCUN motif, which complexes Cu 2+ and Ni 2+ ions (Grogan et al 2001). 134 Furthermore, two Zn 2+ -binding motifs (HEXXH) are present in histatin 1, and one such motif is present in histatins 3 and 5. Complexation of metal ions may eliminate cofactors for enzymes and trace elements for microbial growth.…”
Section: Histatins: Candidacidal and Wound-closure Stimulating Amps Imentioning
confidence: 99%
“…Hst 5 binds Zn and Cu (71) and possesses definitive metal binding motifs (Fig. 1) for Cu and Ni (ACTUN motif, encompassing the first 3 N-terminal amino acids, Asp-SerHis) as well as for Zn (HEXXH motif at the C terminus [72,73]). Multiple strong binding sites within the binding motif are believed to occur for Cu, while Zn has only one strong putative metal binding site (74).…”
Section: Hst 5 Metal Binding Abilities As a Potential Candidacidal Mementioning
confidence: 99%
“…In fact Melino et al [20] have demonstrated that the peptide in the presence of zinc ions is able to aggregate and fuse negatively charged unilamellar vesicles and subsequently it has been reported that histatin-5 binds copper and nickel through its N-terminal ATCUN motif [21].…”
mentioning
confidence: 99%